Ultrafast acoustoelectric effects in semiconductor devices - Heywood, Sarah Louise (2016)
This thesis discusses experiments that have been performed to investigate ultrafast acoustoelectric effects in semiconductor devices. Current commonly employed techniques to generate ultrafast acoustic pulses and detect them with spectral resolution require a powerful pulsed laser system that is bulky, expensive and complicated. If the acoustic pulses could instead be generated and detected by electrical methods, picosecond acoustic techniques could become more readily available as a tool for other users. This thesis focusses on the electrical detection of acoustic pulses with spectral resolution. In many of the key experiments described in this thesis a picosecond strain pulse was generated optically on the opposite face of the sample to the semiconductor device of interest. The strain was generated either in a thin Al film thermally deposited on the sample surface, or directly in the GaAs substrate. Acoustic phonons generated by this method propagated across the substrate to the device. Transient voltages across the semiconductor device caused by the incident phonons were detected using a high frequency real-time oscilloscope. The first evidence of heterodyne mixing of coherent acoustic phonons with microwaves was obtained, for frequencies up to about 100 GHz. First, it was confirmed that Schottky diodes can produce a fast transient voltage in response to an incident acoustic wavepacket. The detection process occurs at the semiconductor-metal interface, and is due to the deformation potential. Bow-tie antenna fabricated directly onto the GaAs substrate proved to be ineffective at coupling microwaves from free space to the Schottky diode. A waveguide-coupled beam-lead Schottky diode provided by e2v had a sufficient response to the incident microwaves to proceed with the mixing experiments. The microwave local oscillator signal was mixed with a tunable narrow frequency band acoustic signal that was produced using a Fabry-Perot etalon external to the laser cavity. The intermediate frequency components were in the range of 1-12 GHz, which could be detected on the oscilloscope. Mixing was performed using both the fundamental frequency acoustic wave and the second harmonic generated in the sample. Semiconductor superlattices were also investigated as electrical detectors for ultrafast acoustic pulses. In this case, the transient voltage measured across the device contained an unexpected contribution in the form of a peak with a width of approximately 2 ns. This signal is too slow to be caused by a strain pulse and too fast for a heat pulse. It is proposed that this peak is caused by long-lived phonon modes from the centre of the mini-Brillouin zone being confined in the superlattice due to Bragg reflections. The peak caused by confined phonons and the two peaks caused by heat pulses also present in the detected signal were investigated for a range of experimental conditions. This allowed comparisons to be made to previous works. A similar superlattice structure had a very different response to the incident acoustic wavepacket. The polarity of the transient voltage detected was inverted and there was no evidence of an electronic response to the confined phonon modes, which would have been present in both samples. It is proposed that the barriers of the NU1727 superlattice sample are thicker than expected, and this strongly affects the electron transport through the structure. This thesis shows that semiconductor devices can be suitable for the electrical detection of ultrafast strain pulses. For this technique to reach its full potential, it is also necessary to be able to generate these strain pulses electrically. A step recovery diode has been considered for this purpose as part of the suggested future work.